1989
DOI: 10.1002/jbmr.5650040118
|View full text |Cite
|
Sign up to set email alerts
|

Cosecretion of calcitonin and calcitonin gene-related peptide from cultured rat medullary thyroid C cells

Abstract: Whether C cells cosecrete calcitonin (CT) and CGRP was examined by exposing cultured rat medullary thyroid carcinoma 6-23 cells for 2 h to high medium Ca and to agents with a potential for affecting Ca-dependent secretion. In every experiment exposure of cells to high medium Ca (2.0-2.5 mM) provoked an increased release of both peptides that was highly correlated (r = 0.73). With other test substances, also, changes in both hormones occurred in parallel. The Ca-channel activator, BAY-K-8644 (10 microM) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, there are no enough evidences on the benefits of long-term using these drugs or up-regulating these biological factors. In the 1980s, some in vitro experiments observed that increased calcium concentrations could stimulate the secretion of CGRP in thyroid cell (Cooper et al, 1985;Haller-Brem et al, 1987;Ohashi et al, 1986;Seitz and Cooper, 1989). During the same period, an in vivo rat experiment indicated that neuronal CGRP levels were positively related to calcium intake (DiPette et al, 1988).…”
Section: Introductionmentioning
confidence: 94%
“…However, there are no enough evidences on the benefits of long-term using these drugs or up-regulating these biological factors. In the 1980s, some in vitro experiments observed that increased calcium concentrations could stimulate the secretion of CGRP in thyroid cell (Cooper et al, 1985;Haller-Brem et al, 1987;Ohashi et al, 1986;Seitz and Cooper, 1989). During the same period, an in vivo rat experiment indicated that neuronal CGRP levels were positively related to calcium intake (DiPette et al, 1988).…”
Section: Introductionmentioning
confidence: 94%